Green synthesis, characterisation and bioactivity of iron oxide nanoparticles using Myristica fragrans leaf extract - Sajna Salim; Neethu Hari; Surabhi Sudhi; Ananthakrishnan Jayakumaran Nair (The Microbe)
The development of environmentally friendly nanomaterials has garnered significant attention due to their potential in biomedical and environmental applications. This study reports the green synthesis of iron oxide nanoparticles (IONPs) using Myristica fragrans leaf extract as a natural reducing and stabilising agent, offering a sustainable and low-cost alternative to conventional chemical methods. The formation of nanoparticles was confirmed by a visible colour change and a UV–Vis absorbance peak at 292 nm, indicative of iron oxide ligand interactions. FTIR analysis revealed the involvement of phenolic and hydroxyl groups in the reduction and stabilisation processes, while SEM imaging showed polydisperse, aggregated nanoparticles with irregular morphology. XRD analysis displayed a broad peak at 24.1°, indicating an amorphous structure, and zeta potential measurement (– 65.2 mV) confirmed high colloidal stability. The nanoparticles exhibited significant antioxidant activity with an IC50 value of 40.88 µg/mL, indicating a strong radical scavenging activity. The nanoparticle exhibited antibacterial activities against Gram-negative Escherichia coli (MTCC 1302) and Gram-positive Bacillus subtilis (MTCC 8322), along with 85.59 % methylene blue dye removal efficiency within 180 min. The chitosan-modified IONPs demonstrated enhanced dispersibility and performance, supporting their applicability in water treatment. These findings underscore the potential of M. fragrans mediated IONPs as a multifunctional and sustainable nanomaterial for environmental remediation.